Amifostine protective effect on cisplatin-treated rat testis - Lirdi, Leandra Campos (2008)
Cisplatin is a potent drug used in clinical oncology but causes spermatogenesis damage. Amifostine is a drug used against toxicity caused by ionizing irradiation and chemotherapeutic drugs. Since cisplatin provokes fertility and induces germ cell apoptosis and necrosis, we proposed to evaluate the amifostine cytoprotective action on testes of cisplatin-treated rats. Thirty-day-old prepubertal Wistar rats received a single cisplatin dose of 5 mg/kg and were killed after 3, 6, and 12 hr. The hematoxylin-eosin stained testicular sections were submitted to histological, morphometric, and stereological analysis. The terminal deoxynucleotidyl transferase-mediated deoxyuridinetriphosphate nick end-labeling (TUNEL) method was used to label apoptotic cells. TUNEL-positive and TUNEL-negative germ cells with abnormal nuclear morphology (ANM) were scored. Significant alterations of greater part of the parameters occurred in the cisplatin-treated group (CE) compared to the group that received amifostine before the cisplatin-treatment (ACE); however, testicular weight and volume did not vary between these groups. Tubular diameter was reduced in CE in comparison to ACE rats, while interstitial tissue and lymphatic space volume and volume density were significantly higher in CE rats; interstitial testicular edema probably occurred in cisplatin-treated rats. CE rats showed important histological alterations, which were more accentuated than in ACE rats. The numerical densities of apoptotic germ cells and TUNEL-negative cells with ANM were lower in ACE than in CE rats. In conclusion, the amifostine previously administered to prepubertal rats reduced the testicular damage caused by cisplatin. We conclude that amifostine partially protected the rat seminiferous epithelium against cisplatin toxicity.